Antitrust : the person-centred approach - Al-Ameen, Abayomi (Cham : Springer, 2014)
This book proposes a different approach to theorising and analysing antitrust issues, working on the premise that at present, antitrust is addressed from top-down and narrow perspectives which in effect limit the attention paid to or exclude issues that could otherwise be considered. This reasoning is motivated by the pursuit of inclusiveness and broadness in the antitrust context. The work contends that traditional top-down antitrust theories are weak because they are incomplete and insufficient in their description and analysis of antitrust issues. Thus, it identifies the need to construct a bottom-up approach. Invariably, such an approach would have to avoid ex ante judgments about the suitability of the normative contents of antitrust laws and theories, lest it fall into the same trap that plagues traditional theories. As a possible solution, the author proposes a procedural account referred to as the person-centred approach (built on theories such as Sen's Capability) and carefully reviews its practicality.
Antitrust : the'other' mode of analysis -- Person-centred approach -- Antitrust rights -- Capability approach : the framework for the person-centred analysis -- Antitrust pluralism and justice -- Person-centred approach and antitrust enforcement.
Thesis (doctoral)--Swansea University, 2012.
Includes bibliographical references (pages 209-214).
Keywords: Antitrust law